Prospects of applying artificial intelligence to determine students’ mental health status in school education - Wenli Liu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Development and progress in any sector are critical in today's ever changing world. People who work in the sports sector believe sports to be extremely important in their life. Football, basketball, cricket, tennis, and other sports are particularly popular among males. When dealing with diverse difficulties, organisational behaviour also refers to an organization's attitude and behaviour. To perform at their best, players must be inspired, encouraged, and trained. The first factor that influences the growth of the sports sector is organisational behaviour. Artificial intelligence is the second factor that contributes to the progress of the sports business. Marketing is the third aspect that contributes to the growth of the sports sector. Any industry's worth and value are increased through marketing. Organizational behaviour, artificial intelligence, and marketing tactics were employed as independent factors in this study. New Product Development, on the other hand, has been employed as a dependent variable. The information was gathered from 30 people and evaluated with AMOS 26v. Furthermore, the findings revealed a substantial relationship between the factors.